1999
DOI: 10.1086/316399
|View full text |Cite
|
Sign up to set email alerts
|

γ Doradus Stars: Defining a New Class of Pulsating Variables

Abstract: In this paper we describe a new class of pulsating stars, the prototype of which is the bright, early, F-type dwarf, γ Doradus. These stars typically have between 1 and 5 periods ranging from 0.4 to 3 days with photometric amplitudes up to 0. m 1 in Johnson V . The mechanism for these observed variations is high-order, low-degree, non-radial, gravity-mode pulsation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
194
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(202 citation statements)
references
References 18 publications
8
194
0
Order By: Relevance
“…The g Doradus class varies via g-mode pulsations with one or more periods between 0.4 and 3 days and amplitudes of . These stars are found among spectral types V Շ 0.1 A7-F5 and luminosity classes V-IV, placing them on the H-R diagram near the red edge of the d Scuti instability strip (Kaye et al 1999). The typical amplitudes of g Doradus stars are detectable for the bright stars in our survey and should show periodic variations.…”
Section: Pulsating Variablesmentioning
confidence: 55%
“…The g Doradus class varies via g-mode pulsations with one or more periods between 0.4 and 3 days and amplitudes of . These stars are found among spectral types V Շ 0.1 A7-F5 and luminosity classes V-IV, placing them on the H-R diagram near the red edge of the d Scuti instability strip (Kaye et al 1999). The typical amplitudes of g Doradus stars are detectable for the bright stars in our survey and should show periodic variations.…”
Section: Pulsating Variablesmentioning
confidence: 55%
“…Handler 1999;Kaye et al 1999;Cuypers et al 2009), space-based observations revealed dozens to hundreds of oscillation frequencies for each star. This in principle should allow the detection of period spacing patterns.…”
Section: The Methodologymentioning
confidence: 99%
“…They cover the transition region between low-mass stars possessing radiative cores and convective envelopes to high-mass stars which have convective cores and radiative envelopes. γ Doradus pulsators exhibit non-radial gravity (g) and / or gravito-inertial modes, with observed pulsation periods between 0.3 and 3 days (Kaye et al 1999), that are excited by the convective flux blocking mechanism at the bottom of the con-vective envelope (Guzik et al 2000;Dupret et al 2005). These pulsations are most sensitive to the characteristics of the deep stellar interior.…”
Section: Introductionmentioning
confidence: 99%